2019
DOI: 10.1037/cpp0000297
|View full text |Cite
|
Sign up to set email alerts
|

The Gender Minority Stress and Resilience Measure: Psychometric validity of an adolescent extension.

Abstract: Objective: Minority stress contributes to several physical and psychological problems in sexual and gender minorities but is largely understudied in transgender/gendernonconforming (TGNC) individuals, particularly TGNC adolescents. The availability of psychometrically sound measures of adolescent minority stress can help improve assessment and treatment planning in this area. This original research study examined whether an existing measure of TGNC-related minority stress and resilience among adults could reta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 32 publications
5
44
0
Order By: Relevance
“…Our search identified 14 studies ( Table 4 ) which met our criteria (see Figure 1 ), including a total of 4.913 trans persons ( 17 , 36 40 , 42 – 45 , 47 50 ). In almost all cases, participants' inclusion was assessed through self-identification as “transgender,” “trans men” or “trans women” ( 17 , 37 40 , 42 46 , 48 , 50 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our search identified 14 studies ( Table 4 ) which met our criteria (see Figure 1 ), including a total of 4.913 trans persons ( 17 , 36 40 , 42 – 45 , 47 50 ). In almost all cases, participants' inclusion was assessed through self-identification as “transgender,” “trans men” or “trans women” ( 17 , 37 40 , 42 46 , 48 , 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our search identified 14 studies ( Table 4 ) which met our criteria (see Figure 1 ), including a total of 4.913 trans persons ( 17 , 36 40 , 42 – 45 , 47 50 ). In almost all cases, participants' inclusion was assessed through self-identification as “transgender,” “trans men” or “trans women” ( 17 , 37 40 , 42 46 , 48 , 50 ). While seven studies included mostly trans women ( 37 , 38 , 40 , 45 – 48 , 50 ), four included more trans men ( 17 , 42 , 44 ) and in one study most participants identified as non-binary [Transgender participants were considered non-binary if they reported a gender identity that was anything other than exclusively male or female, (40, p. 339)].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(33) Even when there is inherent resilience, the effort required to cope with stigma over time may diminish an individual's psychological resources, which may have negative consequences for both their mental and their physical health, according to Hatzenbuehler et al (31) In response to overwhelming evidence of higher observed rates of mental disorders among gay, lesbian and bisexual people compared to heterosexual people, Meyer developed the minority stress theory in 2003 to account for the contributions of stigmaboth enacted and internalized -to mental health for sexual minorities. (34) Meyer's theory, which has recently been adapted to the study of health disparities among gender minorities, (35,36) including transgender adolescents, (37) holds that minorities experience unequal health outcomes because of chronic enacted, internalized and structural stigma experienced alongside other social and structural determinants of health. (38) The theory considers that sexual or gender minority status itself does not confer psychological distress that leads to worse health outcomes.…”
Section: Social Determinants Of Mental Health and The Role Of Stigmamentioning
confidence: 99%